Digital magnetic resonance spectrometer (DMRS) from CIERMag: calibration and relaxometry measurements methodology - Teixeira, Julia Marcolan (2023)
Nuclear Magnetic Resonance (NMR) has become a powerful and ubiquitous analytical tool scientific and technological areas, such as medicine, industry, agriculture, materials science, etc. However, according to a review by Centro de Imagens e Espectroscopia por Ressonância Magnética (CIERMag), although practical to use in most applications, current NMR commercial equipment are restrictive for modifications and does not allow new pulse sequences, or pulse shapes - i.e. adiabatic pulses - to be introduced easily. To avoid these limitations present in commercial NMR equipment the CIERMag group developed the Digital Magnetic Resonance Spectrometer (DMRS) based on Field-Programmable Gate Arrays (FPGAs), and a software based on the Python Magnetic Resonance Framework (PyMR) for planning and control of the experiment. This development included an Integrated Development Environment (IDE), a graphical instruction interface, the Console for acquiring, organizing, visualizing and storing data, a primitive F language, used to develop the pulse sequences, which has a compiler and a language-sensitive editor. In CIERMag context, an NMR Method represents an experiment project as a modern software project, containing all information about the experiment from pre-processing to post-processing. In this study, NMR Methods for DMRS calibration such as spectrometers resonance frequency adjustment, and flip angle (B1 amplitude) calibration were developed, in addition to the implementation of classic NMR sequences such as Carr-Purcell-Meiboom- Gill (CPMG) and Inversion Recovery (IR). The relaxation times of water at 35°C were calculated with the use of CPMG and Inversion recovery sequences. The values for the spin-spin and spin-lattice relaxation times are respectively T2 = 2.095 ± 0.006 s and T1 = 3.49±0.05 s. In addition, as predicted by the literature, we found linear relationships between the concentrations of copper sulfate in water for four different samples with the inverse of the transverse and longitudinal relaxation times. A survey on the influence of temperature variation on the spectrometer operating frequency is also provided. The results for the calibration methodologies comply with the pre-experiment adjustments necessary for measurement reliability. Furthermore, measurements of relaxation times that are following the literature demonstrate that the equipment is functional and ready for use. Therefore, DMRS is an alternative that avoids obsolescence and simplifies the development of new NMR techniques.